Buddhism in five minutes - Harris, Elizabeth J. (Religion in five minutes, 2021)
Introduction / Elizabeth J. Harris -- Part I: Buddhism as a Religion: Is Buddhism a religion? / Denise Cush -- What is the role and focus of faith in Buddhism? / Asanga Tilakaratne -- What is the role of ritual in Buddhism? / Asanga Tilakaratne -- Are relics important to Buddhists? / Kevin Trainor -- What are the holy texts of Buddhism? / Asanga Tilakaratne -- What is the place of images in Buddhism? / Sarah Shaw -- What is the role of narrative in Buddhism? / Brian Black -- Is Buddhism atheistic, non-theistic, or theistic? / Peter Harvey -- Part II: The Buddha: What do we know of the historical Buddha? / Dhivan Jones -- How is the nature of Buddhahood to be understood? / Christopher V. Jones -- How does one 'read' a Buddha-image? / Ronit Wang -- Who is the fat Buddha figure? / Pauline Kolata -- What is a Bodhisattva? / Jiancheng Shi -- How do Buddhists show their devotion to the Buddha? / Paulina Kolata -- Part III: What the Buddha Taught (1): Can we know what the historical Buddha taught? / Rupert Gethin -- What part does belief in rebirth play in Buddhism? / Peter Harvey -- Does Buddhism see the mind as separate from the body? / Peter Harvey -- Do Buddhists see all that happens to one as due to karma? / Peter Harvey -- What is seen as reborn, according to Buddhism? / Peter Harvey -- To what extent does Buddhism "deny the self"? The non-Self teaching / Christopher V. Jones -- What are the "Four Noble Truths" about? / Arjuna Ranatunga -- What does non-attachment mean in Buddhism? / Dhivan Jones -- What is Nirvana? / Arjuna Ranatunga -- What is it to be "enlightened" or "awakened"? / Peter Harvey -- What kinds of "Saints" does Buddhism have? / Arjuna Ranatunga --